Clinical impacts of the concomitant use of L-asparaginase and total parenteral nutrition containing L-aspartic acid in patients with acute lymphoblastic leukemia - Ko, Minoh; Kim, Myeong Gyu; Yoon, Sung-Soo; Kim, In-Wha; Suh, Sung Yun; Cho, Yoon-Sook; Oh, Jung Mi (Frontiers in Nutrition, 2023)
The activity of L-asparaginase (ASNase), one of the essential drugs for the treatment of acute lymphoblastic leukemia (ALL), is competitively inhibited by aspartic acid (Asp). While many commercially used total parenteral nutrition (TPN) products contain Asp, it is not known whether ALL patients treated with ASNase can concomitantly use TPN containing Asp (Asp-TPN). This propensity-matched retrospective cohort study evaluated the clinical effects of the interaction between ASNase and Asp-TPN. A total of 112 ALL patients who were admitted to Seoul National University Hospital in Korea were included in the analysis; 34 received Asp-TPN and ASNase simultaneously. After propensity score matching, 30 patients in each group remained. Concomitant use of Asp and ASNase did not affect the overall response rate (Asp-TPN group [67.9%] versus Control [79.3%]; p = 0.65) and the complete response rate (Asp-TPN group [35.7%] versus Control [34.5%]; p = 1.00) of the ASNase-including induction therapy. Not only response but also relapse was not impacted by concomitant use of ASNase, and Asp-TPN (6-month and 1-year relapse-free survival RFS] odds ratio [OR] 1.00; 95% confidence interval [CI] = 0.36–2.78 and OR 1.24; 95% CI, 0.50–3.12, respectively). The peak levels of each liver function test (LFT) and the frequency of the LFT elevation were evaluated during the induction therapy, which showed no difference between the two groups. In conclusion, no clear rationale for avoiding Asp-TPN in ASNase-treated patients exists.